2022
DOI: 10.3389/fevo.2022.849195
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights Into the Unique Demographic History and Genetic Structure of Five Hmong-Mien-Speaking Miao and Yao Populations in Southwest China

Abstract: Southern China was the original center of multiple ancestral populations related to modern Hmong-Mien, Tai-Kadai, Austroasiatic, and Austronesian people. More recent genetic surveys have focused on the fine-scale genetic structure and admixture history of southern Chinese populations, but the genetic formation and diversification of Hmong-Mien speakers are far from clear due to the sparse genetic sampling. Here, we reported nearly 700,000 single-nucleotide polymorphisms (SNPs) data from 130 Guizhou Miao and Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Recently, the reported 500-year-old Gaohuahua population was found to be genetically related to the HM ancestry [ 8 ]. Still, a recent study of genome-wide SNPs in the present-day HM populations showed that the Libo Yao is more representative of the ancestral lineage of HM groups than the 500-year-old Gaohuahua [ 27 ]. There is a growing number of genome-wide studies of HM-speaking populations, and they all revealed a north–south mixing pattern of HM-speaking people and the existence of genetic substructures among HM-speaking populations from different regions [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the reported 500-year-old Gaohuahua population was found to be genetically related to the HM ancestry [ 8 ]. Still, a recent study of genome-wide SNPs in the present-day HM populations showed that the Libo Yao is more representative of the ancestral lineage of HM groups than the 500-year-old Gaohuahua [ 27 ]. There is a growing number of genome-wide studies of HM-speaking populations, and they all revealed a north–south mixing pattern of HM-speaking people and the existence of genetic substructures among HM-speaking populations from different regions [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Still, a recent study of genome-wide SNPs in the present-day HM populations showed that the Libo Yao is more representative of the ancestral lineage of HM groups than the 500-year-old Gaohuahua [ 27 ]. There is a growing number of genome-wide studies of HM-speaking populations, and they all revealed a north–south mixing pattern of HM-speaking people and the existence of genetic substructures among HM-speaking populations from different regions [ 27 29 ]. Gao et al extrapolated the divergence time of HM-speaking people and found that the separation of Yao from other HM groups was earlier than that between Miao and She.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, excess rare alleles have been found in the Hmong population that could be explained by accumulated mutations over time or through genetic drift caused by significant losses in the Hmong population due to wars ( Listman et al, 2011 ). Analysis of 537 Hmong-Mien speaking individuals using mitochondrial DNA demonstrated variable ratios of lineages that implied Hmong-Mien populations had more genetic contacts with Northern East Asians compared to Southern East Asians ( Wen et al, 2005 ; Yang et al, 2022 ). Hmong kinship practices could contribute as well, including clan hospitality (treating people with the same last name as family), clan exogamy (marrying outside one’s clan), ethnic endogamy (marrying within one’s ethnic group) ( Lee, 2020 ), as well as cross-cousin marriage ( Culhane-Pera et al, 2003 ).…”
Section: Genomics and Pgx Research In Hmongmentioning
confidence: 99%
“…Recently, the reported 500-year-old Gaohuahua population was found to be genetically related to the HM ancestry (Wang, et al 2021b). Still, a recent study of genome-wide SNPs in the present-day Miaos showed that the Libo Yao is more representative of the Miao ancestral lineage than the 500-year-old Gaohuahua (Yang, et al 2022). There is a growing number of genome-wide studies of HM-speaking populations, and they all reveal a north-south mixing pattern of HM-speaking people and the existence of genetic substructures among HM-speaking populations from different regions ( groups was earlier than that between Miao and She.…”
Section: Introductionmentioning
confidence: 99%